An annotated and illustrated cataloque of species of interest to fisheries known to date - Food and Agriculture Organization of the United Nations (FAO) (Rome, 1991)
This is the 13th issue in the FAO series of world-wide annotated and illustrated catalogues of major groups of organisms that enter marine fisheries. The present volumn on marine lobster includes 149 species in 3 infraoders, 10 families and 33 genera.
Keywords: Crustacea,Lobster fisheries,Tôm hùm, thủy sản,Giáp xác